Postmodernism and Post Structuralism: A Literary Dichotomy - Tumbahang, Mohan Kumar (Dristikon: A Multidisciplinary Journal, 2021)
This article entitled 'Postmodern and Post Structuralism: A Literary Dichotomy' has fairly attempted to compare and contrast between the most discussed and comprehensive notions of postmodernism and post structuralism in a possible precise form. In addition, the study focuses on dichotomies of these trends against their respective pre-forms, 'modernism' and 'structuralism' as well. Their tendencies in literary creation and theory have been briefly discussed. The study method it has availed is essentially the qualitative research design which is concerned with establishing answers to 'why' and 'how' of the study in question. The writing is based on the views on the foreign writers, scholars and critics in different published materials or the online resources. The views forwarded by the aforementioned personalities have been duly considered and cited in both types of citations-direct as well as paraphrased versions. This study has followed the comparison and contrast as its theory. After the discussion or analysis, the findings have been deducted that these two terms are confusing especially for the beginners because there are certain similarities as well as dissimilarities between them in specific cases. The study is expected to be helpful for both the teacher and students of literature especially in the field pedagogy or the individuals who are not directly related to pedagogical issue.